Charges Of Indonesia Labor / Workers Against Proper Living Needs That Can Meet The Minimum Wage - Agustuti Handayani (International Multidiciplinary Conference on Social Sciences (IMCoSS), 2015)
The Proper Living Needs (PLN) is a standard requirement that must be fulfilled by an employee or single worker to live both physically and non-physically and socially in a proper condition for the needs of one (1) month.PLN is as a basis in determining the minimum wage as an increase of the minimum necessities for workers life. Wage is one of the instruments that can directly improve the living standard of the worker and his family. The high or low level of wage received by a worker will directly influence the welfare changes experienced by a worker.What drives the worker to be passionate to work effectively? Seeing the different interests among those involved in wages policy, it is not surprising that the wages policy is the result of bargaining the interests from the governments, the employers and workers who directly receive a wage increase.